If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3c + 23c + 40 = 0 Reorder the terms: 40 + 3c + 23c = 0 Combine like terms: 3c + 23c = 26c 40 + 26c = 0 Solving 40 + 26c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-40' to each side of the equation. 40 + -40 + 26c = 0 + -40 Combine like terms: 40 + -40 = 0 0 + 26c = 0 + -40 26c = 0 + -40 Combine like terms: 0 + -40 = -40 26c = -40 Divide each side by '26'. c = -1.538461538 Simplifying c = -1.538461538
| 99-99=0 | | 4x-2(-4)=12 | | 2(t-3)+8t=5(2t+3)-11 | | 45s^2+100st+55t^2=0 | | 4(m-3)=3m+5 | | 2(x+3)+xy=4-(x+13)+xy | | -16w^2+36w+70=0 | | -5x-2y=-16 | | 44.59=9g+3.82 | | 1.4t=56 | | 4(-4)-2y=12 | | 1.44g-3=0.60 | | 7x=31+-2y | | 6(5-2g)-3(-p+7)= | | 6(2x+9)=(6x+12) | | 4v^2+24v+27=0 | | -44-6x=-x+16 | | H=-5t^2+80 | | -7x-8y=-20 | | y+8-3x-4=x-4x+2 | | 61+x=70 | | 7x-10.2=3.8 | | -30+7x=10+9x | | 0=2x^4-15x^2+7 | | 18b^4-39b^3+20b^2=0 | | 15-x=2x-3 | | 8x-154-3x=237+3x | | -5(r+8)=-92 | | 4(-4+k)+8(6+3j)= | | 7x+3y=73 | | 6log(4x-3)=18 | | 74+6x=-31+x |